Bulk metallic glasses - Suryanarayana, C.; Inoue, Akihisa (CRC Press, 2018)
"Reflecting the fast pace of research in the field, the Second Edition of Bulk Metallic Glasses has been thoroughly updated and remains essential reading on the subject. It incorporates major advances in glass forming ability, corrosion behavior, and mechanical properties. Several of the newly proposed criteria to predict the glass-forming ability of alloys have been discussed. All other areas covered in this book have been updated, with special emphasis on topics where significant advances have occurred. These include processing of hierarchical surface structures and synthesis of nanophase composites using the chemical behavior of bulk metallic glasses and the development of novel bulk metallic glasses with high-strength and high-ductility and superelastic behavior. New topics such as high-entropy bulk metallic glasses, nanoporous alloys, novel nanocrystalline alloys, and soft magnetic glassy alloys with high saturation magnetization have also been discussed. Novel applications, such as metallic glassy screw bolts, surface coatings, hyperthermia glasses, ultra-thin mirrors and pressure sensors, mobile phone casing, and degradable biomedical materials, are described. Authored by the world's foremost experts on bulk metallic glasses, this new edition endures as an indispensable reference and continues to be a one-stop resource on all aspects of bulk metallic glasses."--Provided by publisher
Keywords: Metallic glasses.; Bulk solids.; elektronické knihy; electronic books